2019
DOI: 10.7717/peerj.7127
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil properties and fungal community structure in continuous-cropped alfalfa fields in Northeast China

Abstract: To compensate for the seasonal imbalance between livestock and forage yield in the cold region of Northeast China, alfalfa (Medicago sativa L.) continuous cropping has been widely employed in animal husbandry. However, the effects of continuous cropping of alfalfa on soil properties, including physical, chemical and biological properties, are poorly understood. In this study, we investigated the soil properties and fungal community composition of alfalfa fields under continuous cropping for different time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
(78 reference statements)
5
21
0
Order By: Relevance
“…Thus, the increas in soil pH caused by continuous cropping in alkaline soil may have negative roles in regulating soil bacterial diversity. Intriguingly, our previous study revealed that soil fungal phylogenetic diversity and phylotype richness were remarkably increased with the extension of continuous cropping years (Yao et al, 2019), which suggested that the response of soil bacterial and fungal diversity to continuous cropping years are fundamentally different (Bai et al, 2015;. In addition, we observed that bacterial phylogenetic diversity was significantly positively correlated with soil TP, and thus, the decrease in soil TP content after long-term continuous cropping of alfalfa could inhibit microbial diversity and activity (Cleveland and Liptzin, 2007).…”
Section: Long-term Continuous Cropping Of Alfalfa Reduced Bacterial Diversitymentioning
confidence: 58%
See 3 more Smart Citations
“…Thus, the increas in soil pH caused by continuous cropping in alkaline soil may have negative roles in regulating soil bacterial diversity. Intriguingly, our previous study revealed that soil fungal phylogenetic diversity and phylotype richness were remarkably increased with the extension of continuous cropping years (Yao et al, 2019), which suggested that the response of soil bacterial and fungal diversity to continuous cropping years are fundamentally different (Bai et al, 2015;. In addition, we observed that bacterial phylogenetic diversity was significantly positively correlated with soil TP, and thus, the decrease in soil TP content after long-term continuous cropping of alfalfa could inhibit microbial diversity and activity (Cleveland and Liptzin, 2007).…”
Section: Long-term Continuous Cropping Of Alfalfa Reduced Bacterial Diversitymentioning
confidence: 58%
“…The soil DNA used in this study was in line with our previous studies, and was extracted with the Fast DNA ® SPIN Kit for Soil (MP Biomedicals, USA) (Yao et al, 2019).…”
Section: Soil Dna Extraction and Illumina Miseq Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Alfalfa (Medicago sativa L.) is one of the most popular perennial legume forages, and it is known as the "king of the forages", beneficed to its high yield, rich nutritional value and good palatability. This forage is not only the most widely cultivated in the world [1][2][3][4], but also the most widely distributed and economically valuable in China [5,6]. The alfalfa varieties introduced from abroad have the advantages of good quality and high yield, but winter survival rate or spring returning green rate is low, which seriously limits its industrial development in northern China [7].…”
Section: Introductionmentioning
confidence: 99%